The impact of aesthetic therapeutic on the quality of life of women with melasma (Research, Society and Development, 2021)
Melasma is the result of excessive production of melanin, the main pigment that constitutes skin color. It has a multifactorial cause and affects sun-exposed areas of the body, such as the face. Melasma directly impacts the self-esteem of affected patients, impacting their quality of life and social life. The objective: To analyze the benefits of aesthetic treatments in reducing melasma to improve the quality of life of women. This is a descriptive bibliographic research. The results intend to demonstrate the effectiveness of the treatment and the improvement of self-esteem of melasma patients. Conclusion: effective treatments bring benefits to the quality of life of melasma patients. It is suggested that further studies on the subject are carried out and that these researches can present information about the most effective treatments and how they act in clearing melasma.